DIGITAL VIOLENCE AGAINST WOMEN AND GIRLS AS A VIOLATION OF HUMAN RIGHTS: INTERNATIONAL RECOGNITION AND CHALLENGES OF ARTIFICIAL INTELLIGENCE - Furtado de Barros, Renata (Revista Gênero e Interdisciplinaridade, 2026)
The expansion of digital technologies has profoundly transformed social interactions, political participation, and the exercise of fundamental rights. Alongside the benefits provided by the digital environment, technology-mediated gender-based violence has emerged and intensified, disproportionately affecting women and girls. In this context, this article aims to analyze the extent to which International Human Rights Law recognizes digital violence against women and girls as a human rights violation and to identify the main challenges related to their protection in digital environments. The study adopts a qualitative methodology based on bibliographic and documentary research, including the analysis of international treaties, general recommendations, reports issued by international organizations, and specialized literature. Initially, the article examines the historical exclusion of women from the universality of human rights and the construction of gender inequalities. It then analyzes the main international normative frameworks, with emphasis on the Vienna Declaration and Programme of Action, the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), its General Recommendations No. 19 and No. 35, and the Inter-American Convention of Belém do Pará. Finally, it investigates contemporary forms of digital gender-based violence, the international recognition of technology-facilitated gender-based violence, and the challenges posed by generative artificial intelligence. The study concludes that the international society has progressively recognized digital violence as a human rights violation, although significant challenges remain regarding digital governance, platform accountability, and the ethical regulation of artificial intelligence grounded in human rights principles.